Capacitation of canine serological survey team to research visceral Leishmaniasis - Galvão, André Luiz Baptista [UNESP]; De Nardo, Carla Daniela Dan; Neto, Halim Atique; Benitez, Aline do Nascimento; Ribeiro, Cássio Ricardo; Bresciani, Katia Denise Saraiva [UNESP]; Aoki, Vanessa Leyko; dos Santos, Izalco Nuremberg Penha (Universidade Federal do Paraná, 2019)
Visceral Leishmaniasis (VL) is a serious disease and, when not treated can cause 95% death in humans. There is a high prevalence in dogs, with many asymptomatic cases. Early diagnosis in humans and dogs is necessary to map and control this disease in the municipalities. In São Paulo state, the first case was reported in Araçatuba in 1998. Since then, the disease spread especially in the northwest of the state. Due to this concern, São José do Rio Preto City Hall carried out a canine serological survey to research the VL in the first semester of 2017. The students from the Veterinary School of Centro Universitário de Rio Preto (UNIRP) composed the serological survey teams. The training of the survey teams was essential to assure the animal well-being, the quality of the samples used for diagnosis, and health information to the population. The present work aims to describe the methodology used for the training of the survey teams. The capacitation was done through theoretical explanation and description of the methods. The practice was carried out by supervised individual orientation using canine mannequins. Twenty students from the survey team taught tutors and their dogs, residents in the urban area of the municipality, from April to May 2017. A thousand five hundred and eighty one blood samples from the dogs were collected. There were no violations registered that could present any risk to the animals or humans well-being during the action. The training optimized the time to collect blood samples from dogs in urban area as public health strategy.
Capacitação de equipes para inquérito sorológico canino para pesquisa de Leishmaniose visceral
Keywords: Blood; Constraint; Mannequin